Risk factors for cardiac implantable electronic device infections: a nationwide Danish study. (20th October 2022) - Olsen, Thomas; Jørgensen, Ole Dan; Nielsen, Jens Cosedis; Thøgersen, Anna Margrethe; Philbert, Berit Thornvig; Frausing, Maria Hee Jung Park; Sandgaard, Niels Christian Foldager; Johansen, Jens Brock
Abstract: Aims: Cardiac implantable electronic device (CIED) infection is a severe complication to modern management of cardiac arrhythmias. The CIED type and the type of surgery are recognized as risk factors for CIED infections, but knowledge of patient-related risk factors is scarce. This study aimed to identify lifelong patient-related risk factors for CIED infections. Methods and results: Consecutive Danish patients undergoing a CIED implantation or reoperation between January 1996 and April 2018 were included. The cohort consisted of 84 429 patients undergoing 108 494 CIED surgeries with a combined follow-up of 458 257 CIED-years. A total of 1556 CIED explantations were classified as either pocket ( n = 1022) or systemic CIED infection ( n = 534). Data were cross-linked with records from the Danish National Patient Registry and the Danish National Prescription Registry. Using multiple-record and multiple-event per subject proportional hazard analysis, specific patient-related risk factors were identified but with several variations amongst the subtypes of CIED infection. CIED reoperations were associated with the highest risk of pocket CIED infection but also CIED type, young age, and prior valvular surgery [hazard ratio (HR): 1.62, 95% confidence interval (CI): 1.29–2.04]. Severe renal insufficiency/dialysis (HR: 2.40, 95% CI: 1.65–3.49), dermatitis (HR: 2.80, 95% CI: 1.92–4.05), and prior valvular surgery (HR: 2.09, 95% CI: 1.59–2.75) were associated with the highest risk of systemic CIED infections. Congestive heart failure, ischaemic heart disease, malignancy, chronic obstructive pulmonary disease, and temporary pacing were not significant at multivariate analysis. Conclusion: Specific comorbidities and surgical procedures were associated with a higher risk of CIED infections but with variations amongst pocket and systemic CIED infection. Pocket CIED infections were associated with CIED reoperations, young age and more complex type of CIED, whereas systemic CIED infections were associated with risk factors predisposing to bacteraemia. Structured Graphical Abstract: Structured Graphical Abstract